Quality of life and living conditions from the viewpoint of residents in a seniors condominium - Elen Ferraz TESTON; Sonia Silva MARCON
The aim of the study was to understand how residents of a condominium Aging realize the quality and conditions of life in this new housing modality. This is an exploratory qualitative study of 20 elderly residents of the condominium Maringá . Data were collected in February 2012 in the household were semistructured and subjected to content analysis interviews. The results indicate the factors valued by the elderly in their perception of quality of life such as independence, autonomy, having an occupation, developing leisure and acceptance of the aging process activities. Also valued the structure and characteristics of this housing method due to the possibility of social interaction. We conclude that the identification of these aspects allows the planning of strategies for integrated care for the elderly and it is suggested that nurses recognize and value the aspects highlighted in the planning of care with elderly people in general.